EFFECTIVENESS OF COOPERATIVE LEARNING MODEL OF SNOWBALL THROWING TYPE AND COOPERATIVE LEARNING MODEL OF GROUP INVESTIGATION TYPE TOWARD MATHEMATICS LEARNING OUTCOMES IN CLASS VIII OF SMP MUHAMMADIYAH 7 YOGYAKARTA - Nano Gunawan; Aris Thobirin (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
The reason for the research that the learning process uses in SMP Muhammadiyah 7 Yogyakarta tends centered to the teacher, students becoming passive and less involved in the learning process, so that needed model of learning that involved students becoming active. Model of learning that can provide opportunities for students to actively is a cooperative learning model of snowball throwing and cooperative learning model of group investigation. This study aims to determine the effectiveness of the cooperative learning model of snowball throwing type and cooperative learning model of group investigation type toward mathematics learning outcomes in second grade of SMP Muhammadiyah 7 Yogyakarta in odd semester academic year of 2016/2017. The population in this study were all students of class VIII SMP Muhammadiyah 7 Yogyakarta in the first semester of the academic year 2016/2017 is divided seven classes namely class VIII A, VIII B, VIII C, VIII D, VIII E, VIII F, VIII G totaling 150 students. Samples were taken 3 classes using random sampling techniques, derived class VIII B as an experimental class I, VIII D class as the experimental class II, and VIII C class as the control class. Data analysis techniques used for prerequisite tests including normality test with chi-square formula, bartlett homogeneity test by test, and test hypotheses include F test and significant raced different (LSD). The result on significant level 5% and db = (2,98) shows (1) there are different results of the mathematics learning uses model of learning snowball throwing, model of group investigation, and model of learning expository. This is shows with value  ,  so that  and (2) the results mathematics learning of the students that use the cooperative learning model of snowball throwing better than learning process uses cooperative learning model of group investigation and model of learning expository. This result shows with hypothesis test LSD which is significant level 5% and 98 degrees of freedom is obtained in case I because    rejected, and  >  it is mean that . In case II    rejected, and  it is mean that . While in case III    rejected, and  it is mean that . While can concludes as follow .